2018
DOI: 10.1002/1873-3468.13065
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing DNA for functionalization of biomaterial surfaces

Abstract: DNA sequences are widely used for gene transfer into cells including a number of substrate surface-based supporting systems, but due to its singular structure property profile, DNA also offers multiple options for noncanonical applications. The special case of using DNA and oligodeoxyribonucleotide (ODN) structures for surface functionalization of biomedical implants is summarized here with the major focus on (a) immobilization or anchoring of nucleic acid structures on substrate surfaces, (b) incorporation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 97 publications
(233 reference statements)
0
10
0
Order By: Relevance
“…DNA is highly charged which allows for sequestering of biomolecules non-covalently (such as a LBL approach). 255,256 Low immunogenicity and tunable immunomodulation are other benefits of using DNA for bioactivation of dental implant surfaces. 257 Early work for enhanced soft tissue attachment used poly-D-lysine and poly(allylamine) hydrochloride with DNA for LBL coatings on titanium.…”
Section: Growth Factorsmentioning
confidence: 99%
“…DNA is highly charged which allows for sequestering of biomolecules non-covalently (such as a LBL approach). 255,256 Low immunogenicity and tunable immunomodulation are other benefits of using DNA for bioactivation of dental implant surfaces. 257 Early work for enhanced soft tissue attachment used poly-D-lysine and poly(allylamine) hydrochloride with DNA for LBL coatings on titanium.…”
Section: Growth Factorsmentioning
confidence: 99%
“…20 , 21 Finally, the use of oligonucleotide-conjugates as a means to impart bioinstructive properties on a material has emerged as a significant area of research in recent years. 22 , 23 While the natural roles of deoxyribonucleic acid (DNA) and ribonucleic acid (RNA) sequences are difficult to exploit when tethered in the extracellular environment, the structural and functional capabilities of non-natural and evolved sequences are increasingly being employed in biomaterial design. In particular, aptamer sequences able to bind strongly to a target of interest have been used as a means to control the deposition of regenerative proteins, recruit endogenous growth factors, and control cell-selective adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…27 , 28 The biological roles of polypeptide, glycan, and oligonucleotide conjugates and the influence of particular sequences and structures on biological behavior have been reviewed extensively. 18 , 19 , 23 , 27 − 30 Similarly the choice of core scaffold material, topological and physical effects on cell behavior, and the influence of biomaterial degradability and plasticity are equally well documented. 7 , 8 , 31 35 Although briefly covered here as an introduction to the field, the reader is therefore directed to these excellent and comprehensive reviews for further information.…”
Section: Introductionmentioning
confidence: 99%
“…Vascularization is crucial for tissue development, maintenance and regeneration by to supplying nutrients and oxygen for cells and tissue (Santos and Reis, 2010 ; Muangsanit et al, 2018 ). Thus, many different approaches have been used to functionalize the electrospun scaffolds for enhancing vascularization, such as growth factors (Zhao et al, 2016 ; Janse van Rensburg et al, 2017 ), functional molecules (Lee et al, 2015 ; Garcia and Garcia, 2016 ), DNA (Scharnweber et al, 2018 ) and so on. In our previous studies, we demonstrated that an integrin-based ligand modified electrospun scaffold improved EC functions in vitro and vascularization in vivo (Hao et al, 2017 , 2020a ).…”
Section: Introductionmentioning
confidence: 99%